Angular roughshark Oxynotus centrina (Squaliformes: Oxynotidae) in captivity feeding exclusively on elasmobranch eggs: an overlooked feeding niche or a matter of individual taste?. Issue 4 (17th August 2015) - Guallart, J.; García‐Salinas, P.; Ahuir‐Baraja, A. E.; Guimerans, M.; Ellis, J. R.; Roche, M.
<x xml:space="preserve">Abstract</x> A specimen of angular roughshark Oxynotus centrina has been kept successfully in captivity for the first time. Over a period of 24 months, the specimen preyed exclusively on the contents of elasmobranch egg cases, suggesting a specialized trophic niche.